2013
DOI: 10.1016/j.dnarep.2013.04.013
|View full text |Cite
|
Sign up to set email alerts
|

ATM-deficient human neural stem cells as an in vitro model system to study neurodegeneration

Abstract: Loss of ATM kinase, a transducer of the DNA damage response and redox sensor, causes the neurodegenerative disorder ataxia-telangiectasia (A-T). While a great deal of progress has been made in elucidating the ATM-dependent DNA damage response (DDR) network, a key challenge remains in understanding the selective susceptibility of the nervous system to faulty DDR. Several factors appear implicated in the neurodegenerative phenotype in A-T, but which of them plays a crucial role remains unclear, especially since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 48 publications
(31 reference statements)
2
17
0
Order By: Relevance
“…Indeed, OPC derived from Nbs1-CNS -Δ −/− or Atm −/− failed to differentiate into mature OL in culture (Allen et al, 2001; Carlessi et al, 2009; Carlessi et al, 2013; Liu et al, 2014b). In vivo, as early as seven days postnatal, the number of proliferating OPC is significantly reduced and apoptotic OPC increased in the Nbs1-CNS -Δ −/− brain with a resulting loss of myelin proteins including MBP, MOG and PLP in the corpus callosum (Liu et al, 2014a, b).…”
Section: Oligodendrocytes and Myelin Are Vulnerable To Genetic Defmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, OPC derived from Nbs1-CNS -Δ −/− or Atm −/− failed to differentiate into mature OL in culture (Allen et al, 2001; Carlessi et al, 2009; Carlessi et al, 2013; Liu et al, 2014b). In vivo, as early as seven days postnatal, the number of proliferating OPC is significantly reduced and apoptotic OPC increased in the Nbs1-CNS -Δ −/− brain with a resulting loss of myelin proteins including MBP, MOG and PLP in the corpus callosum (Liu et al, 2014a, b).…”
Section: Oligodendrocytes and Myelin Are Vulnerable To Genetic Defmentioning
confidence: 99%
“…Left panel HDAC1/2 and ATM are recruited to the DNA lesions to facilitate NMEJs in age-associated DSBs (Lee and Paull, 2005; Miller et al, 2010). But HDAC1/2 and ATM are also known to promote OL maturation by promoting myelin gene expression (Shen et al, 2008a; Shen et al, 2008b), and OPC differentiation respectively (Allen et al, 2001; Carlessi et al, 2009; Carlessi et al, 2013; Liu et al, 2014b). ATM may affect MyRF expression but the underlying molecular mechanism remains unknown (Liu et al, 2014b).…”
Section: Aging Ols and Their Lineage-specific Dependence On Componmentioning
confidence: 99%
“…Neurological manifestations presented by AT patients resulted from cerebellar atrophy (Carlessi et al. 2013). Neurodegeneration of the cerebellum is progressive and is responsible for unsteady gait, poor muscle control, abnormal eye movements and problems with speaking or swallowing (McKinnon 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This was, to the best of our knowledge and at the time of writing the first exemplification of an iPS cell derived neuronal model of A-T. However this has recently changed [196,212].…”
Section: Discussionmentioning
confidence: 99%
“…These included aberrant regulation of glutamate receptor signaling, CREB signaling and axonal guidance pathways. Interestingly, Carlessi et al [212] showed neuronal differentiation bias after ATM knockdown with neuronal progenitors consistently producing fewer GABAergic neurons. Although we did not quantify the ratios of GLUTAmatergic to GABAergic neurons, the fact that we observe extensive upregulation of genes involved with glutamate receptor signaling may support the notion that such a bias also exists in our cultures.…”
Section: Discussionmentioning
confidence: 99%